Recent Advances on Graphene Quantum Dots: From Chemistry and Physics to Applications. Issue 21 (4th March 2019) - Yan, Yibo; Gong, Jun; Chen, Jie; Zeng, Zhiping; Huang, Wei; Pu, Kanyi; Liu, Jiyang; Chen, Peng
Abstract: Graphene quantum dots (GQDs) that are flat 0D nanomaterials have attracted increasing interest because of their exceptional chemicophysical properties and novel applications in energy conversion and storage, electro/photo/chemical catalysis, flexible devices, sensing, display, imaging, and theranostics. The significant advances in the recent years are summarized with comparative and balanced discussion. The differences between GQDs and other nanomaterials, including their nanocarbon cousins, are emphasized, and the unique advantages of GQDs for specific applications are highlighted. The current challenges and outlook of this growing field are also discussed. Abstract : Graphene quantum dots (GQDs) are flat 0D nanomaterials, promising a wide spectrum of applications. The recent significant advances are summarized with comparative, balanced, and mechanistic discussion. The difference between GQDs and other nanomaterials, and the unique advantages of GQDs for specific applications are highlighted. The current challenges and outlook of this growing field are also discussed.